2017
DOI: 10.3844/ajassp.2017.392.405
|View full text |Cite
|
Sign up to set email alerts
|

Climate Projections of Future Extreme Events in Malaysia

Abstract: In Malaysia, extreme rainfall events are often linked to a number of environmental disasters such as landslides, monsoonal and flash floods. In response to the negative impacts of such disaster, studies assessing the changes and projections of extreme rainfall are vital in order to gather climate change information for better management of hydrological processes. This study investigates the changes and projections of extreme rainfall over Peninsular Malaysia for the period 2081-2100 based on the RCP 6.0 scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Rainfall is anticipated to increase by ~20 to 40% during summer across the Southeast Asia region, as portrayed by the Intergovernmental Panel on Climate Change (IPCC) Special Report on Emission Scenarios (SRES A2, A1B and B2) (Loh et al 2016 ). Syafrina et al ( 2017 ) projected increase in hourly duration and intensity of rainfall for the period 2081–2100 with spatio-temporal variation in the distribution within the Peninsular Malaysia based on the Representative Concentration Pathway (RCP 6.0) scenario.…”
Section: Climate Change and Extreme Weather Eventsmentioning
confidence: 99%
“…Rainfall is anticipated to increase by ~20 to 40% during summer across the Southeast Asia region, as portrayed by the Intergovernmental Panel on Climate Change (IPCC) Special Report on Emission Scenarios (SRES A2, A1B and B2) (Loh et al 2016 ). Syafrina et al ( 2017 ) projected increase in hourly duration and intensity of rainfall for the period 2081–2100 with spatio-temporal variation in the distribution within the Peninsular Malaysia based on the Representative Concentration Pathway (RCP 6.0) scenario.…”
Section: Climate Change and Extreme Weather Eventsmentioning
confidence: 99%
“…NAHRIM [6], on the other hand, forecasted a substantial increase (11 to 43%) in mean monthly rainfall over the area of the east coast of Peninsular Malaysia, while Moyawa et al [7], who conducted a study on 54 stations along the east coast region of Peninsular Malaysia, reported that the heavy rainfall in the studied areas increased by 1.5 days per decade over the time period from 1971 to 2010. Regarding extreme events in Malaysia, Billa et al [8] reported an increase of rainfall intensities during monsoon, which is the major cause for heavy flood and landslide, and this, according to Syafrina et al [9], will be worsened in the future. Extreme events in Malaysia risk human life and damage properties.…”
Section: Introductionmentioning
confidence: 99%
“…A short-term (less than six hours) flash flood resulting from a substantive rainstorm can rapidly raise the water level in rivers and streams. Substantive rainfall incidences in Malaysia are often connected to ecological catastrophe-like flash flooding during monsoon seasons and landslides [15][16][17]. e extent of interactions of differing road networks and other aspects can be assessed to gauge the effect of flooding.…”
Section: Introductionmentioning
confidence: 99%